Autorregulación emocional en adolescentes - Salinas Peralta, Gabriela Alejandra (2016)
The present article shows a review and makes reflections on emotional self-regulation during adolescence in students of the first periods of higher education institutions. Finally, the presence of parents and institutions is considered vital tofacilitate the development of emotional self-regulation and for the prevention of social problems, mental health and dropout.